Madrasah Principal Leadership in Improving the Quality of Education in Madrasah Ibtidaiyah Negeri 3 Tangerang Selatan - Triono, Wahyu; Lesmi, Kirana; Khotimah, Iim (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This study aims to describe the leadership of the madrasa heads towards the quality of education, analysis strategy in improving the quality of education in madrasas, which has described the character of leadership, in improving the quality of madrasah education. This study uses a qualitative method. In data collection techniques using obtained through, interviews, documentation studies, and observation Data analysis with data reduction, data presentation, and verification as well as the conclusion. The results of the research presentation are that there are several strategies for the madrasa head in achieving the goals that have been jointly set by all components of the school. The strategy implemented by the head of the madrasa at Madrasah Ibtidaiyah Negeri 3 Tangerang. Using a theory about the quality of education which consists of input, process, and output as well as outcomes that are already available. Strategy implementation has also been carried out regarding the lead character of the madrasah head, following data sources that lead to democratic leadership. Strategies for improving the quality of education can be seen, and receive ideas and thoughts from related parties in issuing school policies that emphasize the quality of education in madrasas.